Geoelectrical prospecting for a copper-sulfide mineralization in the Camaqua sedimentary basin, Southern Brazil - Cortes, Ariane R. P. [UNESP]; Moreira, Cesar A. [UNESP]; Veloso, Dimitri I. K. [UNESP]; Vieira, Leandro B. [UNESP]; Bergonzoni, Flavio Anauate [UNESP] (Inst Geophysics Unam, 2016)
In this paper are presented the results of the combination between a resistivity method and geological surface mapping, applied to the study of an area with potential mineralization of copper sulfides sited on the northern edge of the Camaqua sedimentary basin, Brazilian southern. The copper mineralization is housted in a metamorphosed, silicified and fractured sandstone with abundant presence of malachite and azurite in the fractured planes of the rock. The geophysical survey in this work consisted of 6 lines of electric resistivity tomography in Wenner-Schlumberger array, of 520 m long and 10 m of space between the electrodes, arranged in a regular grid according to structural criteria previously established. The inversion models show a low resistivity area in a depth of 60 m that can be related to a sulphidation zone. This zone with a somewhat circular shape is aligned in the NW SE direction and is approximately 100 meters long. High resistivity areas around it indicate that it is surrounded by a silicification zones. The evidence for an argillic zone peripheral to the deposit is expressed by the occurrence of abundant copper carbonate in surface, since clay and carbonates are formed from low temperature and final stages of hydrothermal crystallization of the deposit.
Keywords: copper; sulfide; mineralization; hydrothermal; electrical resistivity